The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.jinf.2020.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Route and duration of antibiotic therapy in acute cellulitis: A systematic review and meta-analysis of the effectiveness and harms of antibiotic treatment

Abstract: J (2020) Route and duration of antibiotic therapy in acute cellulitis: a systematic review and meta-analysis of the effectiveness and harms of antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…21 In addition, a systematic review of adult literature found that 30% to 50% of patients eligible for PO therapy receive IV antibiotics and many patients remain on IV antibiotics longer than necessary. 22 Multiple studies included in the review found no difference in treatment effectiveness between IV and PO treatment groups with similar rates of relapse. 23,24 This posits that more children who receive IV antibiotics could be safely discharged on PO antibiotics without increased risk of treatment failure or serious complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition, a systematic review of adult literature found that 30% to 50% of patients eligible for PO therapy receive IV antibiotics and many patients remain on IV antibiotics longer than necessary. 22 Multiple studies included in the review found no difference in treatment effectiveness between IV and PO treatment groups with similar rates of relapse. 23,24 This posits that more children who receive IV antibiotics could be safely discharged on PO antibiotics without increased risk of treatment failure or serious complication.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive bacterial infections are rare in immunocompetent children with uncomplicated cellulitis; one retrospective study of 104 neonates with afebrile skin and soft tissue infections found no evidence of bacteremia 21 . In addition, a systematic review of adult literature found that 30% to 50% of patients eligible for PO therapy receive IV antibiotics and many patients remain on IV antibiotics longer than necessary 22 . Multiple studies included in the review found no difference in treatment effectiveness between IV and PO treatment groups with similar rates of relapse 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…The duration of treatment is usually 5 to 7 days for patients with uncomplicated cellulitis who improve clinically early [70–72,73 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…It also provides an avenue to treat oral antibiotic “treatment failures” without admission. However, the literature does not currently justify parenteral therapy in treating stable SSSI 2,3 . Furthermore, a potential downside is that the cost of the novel antibiotic selected for use in this study, $4,604 per 1500 mg of dalbavancin, may be very limiting for hospitals and patients alike.…”
mentioning
confidence: 96%
“…Once diagnosed with an SSSI the physician can choose between a number of treatments including discharge with oral antibiotics, a single dose of IV antibiotics followed by discharge on oral meds, or just admission for IV therapy. Current literature suggests that these options are noninferior to each other for patients not in shock and without suspicion for necrotizing infections 2 . Still, many physicians choose parenteral therapy for various reasons, including the reasoning that it simply feels safer 3 .…”
mentioning
confidence: 99%